Lithium Metal Anodes: A Lithium Metal Anode Surviving Battery Cycling Above 200 °C (Adv. Mater. 29/2020). Issue 29 (21st July 2020) - Fu, Lin; Wan, Mintao; Zhang, Bao; Yuan, Yifei; Jin, Yang; Wang, Wenyu; Wang, Xiancheng; Li, Yuanjian; Wang, Li; Jiang, Jianjun; Lu, Jun; Sun, Yongming
Abstract : In article number 2000952, Jun Lu, Yongming Sun, and co‐workers report an innovative Li/Li5 B4 composite electrode featuring a 3D Li5 B4 fibrillar framework filled with metallic Li. Benefiting from the effect of capillaries and the physical confinement of the 3D lithiophilic Li5 B4 framework for metallic Li, the Li/Li5 B4 composite electrode maintains its initial structure without leakage of liquid‐metallic Li at 325 °C and survives stable battery cycling above 200 °C with a regular cell configuration.